(untitled) (Web of Teachers: Inderscience Research, 2024)
This study investigates the complex predicate constructions in Uzbek, which possesses a rich variety of light verb constructions. Novel data from Uzbek is provided, and it is analyzed on the basis of proposed criteria in the government and binding theory (GB) literature for complex predicates. The analysis reveals that these constructions express simultaneity, cause and effect, and consecutivity. Both verbs in complex constructions share the same subject, and they describe a single event.